Probability of hyperthermia in a hot environment while wearing a liquid cooling garment underneath firefighters' protective clothing. Issue 4 (4th May 2021) - Aljaroudi, Ali M.; Bhattacharya, Amit; Yorio, Patrick; Strauch, Amanda L.; Quinn, Tyler D.; Williams, W. Jon
Abstract: Firefighters' protective clothing (FPC) can limit human thermoregulation due to limited water vapor permeability and insulation. This study investigated the effect of cooling on the physiological responses and probability of hyperthermia in subjects wearing FPC during exercise in a hot environment. Twelve males participated in this study. A maximal graded treadmill exercise test was performed to measure maximal oxygen uptake ( V ̇ O2max ) and to assess subjects' capacity to perform the assigned exercise. Exercise included treadmill walking at 40% V ̇ O2max in warm (30 °C) and humid (70% RH) conditions for 40 min while wearing FPC. Subjects participated in two randomly counterbalanced assigned experimental protocols: control (no cooling) and intervention (cooling). The experimental intervention consisted of a cooling garment infused with cooled water (18 °C) through silastic tubing sewn into the fabric and worn underneath FPC. Each subject served as their own control and, therefore, completed both the control and intervention of the protocol. A logistic regression model was used to analyze the interaction effect of cooling on the probability of progression to hyperthermia (Tc ≥ 38 °C). Subjects' physiological responses increased during exercise in a warm and humid environment. Active cooling decreased (p < 0.05) the thermal stress thereby reducing the probability of hyperthermia while exercising in hot and humid conditions. The results indicate that when cooling was used each subject, on average, was 91% less likely to reach the lower threshold limit of hyperthermia. Exercise in hot environments while wearing FPC results in significant physiological strain, which may lead to hyperthermia. Utilization of a cooling garment reduced physiological strain and the probability of hyperthermia.